THE USE OF AUTHENTIC PRINTED MEDIA WITH VOCABULARY SELF-COLLECTION STRATEGY (VSS) TECHNIQUE TO TEACH VOCABULARY IN READING NARRATIVE TEXTS TO THE TENTH GRADERS OF SENIOR HIGH SCHOOL 2 SIDOARJO (RETAIN, 2016)
THE USE OF AUTHENTIC PRINTED MEDIA WITH VOCABULARY SELF-COLLECTION STRATEGY (VSS) TECHNIQUE TO TEACH VOCABULARY IN READING NARRATIVE TEXTS TO THE TENTH GRADERS OF SENIOR HIGH SCHOOL 2 SIDOARJO Yovieta Vianindo Soeharto Putri English Education, Faculty of Languages and Arts, State University of Surabaya yovietavianindo@yahoo.com Dra. Theresia Kumalarini M.pd English Education, Faculty of Languages and Arts, State University of Surabaya Kumala_rini52@yahoo.com Abstrak Penelitian ini merupakan penelitian deskriptif kualitatif, yang memiliki tujuan agar peneliti dapat menerapkan metode pengajaran yang memastikan bahwa segala sesuatu terjadi secara alami. Tujuan penelitian ini, guna melihat respon siswa-siwi terhadap metode pembelajaran yang sedikit berbeda, misalnya dengan adanya permainan dalam pembelajaran. Subyek metode pembelajaran ini ditujukan kepada siswa-siswi kelas X di SMA Negeri 2 Sidoarjo. `Metode pembelajaran yang dilakukan oleh peneliti menggunakan kurikulum 2013. Dengan metode penelitian deskriptif kualitatif peneliti menemukan peningkatan minat siswa-siswi melalui wawancara beberapa pertanyaan yang ditujukan kepada peserta didik dan pertanyaan-pertanyaan yang terkait dengan media cetak otentik sebagai tehnik membaca narasi dalam pelajaran bahasa inggris. Pertanyaan-pertanyaan tersebut membantu peneliti untuk mengumpulkan data tentang respon peserta didik terhadap penerapan tehnik media cetak otentik untuk mengajar vocabulary dalam teks narasi. Keywords:Pembelajaran Bahasa , VSS, Strategi, Narrative Text, Keyakinan Abstract This research is a qualitative descriptive study, which has the goal of keeping researchers can apply the teaching method that ensures that everything happens naturally. The purpose of this study, in order to see the response of students against a slightly different learning methods, for example with their play in learning. The subject of this teaching method is addressed to students of tenth graders in Senior High School 2 Sidoarjo. The learning method conducted by researchers using the curriculum of 2013. With descriptive research method qualitative researchers found increased interest students by interviewing some of the questions addressed to students and the questions related to the print media as an authentic narrative technique of reading in English class. Those questions helped the researchers to collect data on the response of learners towards the implementation of an authentic print media techniques to teach vocabulary in narrative text. Keywords : Language Learning, VSS, Strategies, Narrative Text, Belief.